Short Communication: Association of GH, IGF1R, and PIT1 genes polymorphism with average daily gain and body measurement in Pesisir cattle - ARNIM .; TINDA AFRIANI; YURNALIS .; DINO EKA PUTRA (Smujo International, 2018)
Arnim, Yurnalis, Afriani T, Putra DE. 2017. Short Communication: Association of GH, IGF1R, and PIT1 genes polymorphismwith average daily gain and body measurement in Pesisir cattle. Nusantara Bioscience 10: 221-225. Growth hormone (GH) andinsuLin-like growth factor I receptor (IGF1R), and Pit1 gene has important effect on growth, carcass, and meat quality traits in manyspecies. The objectives of the present study were to study the associations of the GH/AluI, GH/MboII, IGF1R/MspI and PIT1/HinfI withgrowth and body measurent such as body length (BL), chest girth (CG), height withers (HW) in Pesisir cattle. A total 175 Pesisir cattlewere used in this study. Weight gain, and body measurement were fitted using the General Linear Model (GLM) procedure of the SASprogram. The resuLts showed significant associations between the CC genotype of the GH/MboII polymorphism and higher weight gainand height withers (p < 0.05). The GH/AluI polymorphism did not have any effect on the weight gain and body measurement. Allelefrequencies were found as A: 0.374 and B: 0.626 in GH/MboII polymorphism in GH gene. The effect of GH/AluI polymorphisms wasnot observed on average daily gain and body measurement in Pesisir cattle (P>0.05). The effect of IGF1R/MSpI polymorphism was notobserved on average daily gain but show significant association between AA and AB genotype and height withers (p < 0.005). ThePIT1/HinfI polymorphism was not associated with average daily gain and body measurement in Pesisir cattle. The resuLts demostratedthat the GH/MboII and GHR1/MspI polymorphisms couLd be used as a candidate gene for selection in Pesisir cattle.